Idiopathic thrombocytopenic purpura associated with an astrocytoma - Samuelson, Clare (BMJ Publishing Group, 2010)
We present the case of an 8-year-old girl with chronic idiopathic thrombocytopenic purpura (ITP) and a short history suggestive of raised intracranial pressure. Urgent computed tomography scan of the head showed a large bleed into a left cerebellar lesion. She underwent treatment with intravenous immunoglobulin (IVIg) and steroids to increase her platelet count, followed by excision of the lesion, which was found to be a benign pilocytic astrocytoma. The patient made a complete recovery and shortly afterwards underwent splenectomy, following which there was complete resolution of her thrombocytopenia.